2020
DOI: 10.1111/ger.12499
|View full text |Cite
|
Sign up to set email alerts
|

A five‐step risk management process for geriatric dental practice during SARS‐CoV‐2 pandemic

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is an RNA virus that causes coronavirus infection (COVID‐19). COVID‐19 is a highly contagious disease transmitted through respiratory droplets, saliva and other contact routes. Within 10 months of its outbreak, SARS‐CoV‐2 has infected more than 23 million people around the world. Evidence suggests that older adults are the most vulnerable to infection and have an increased risk of mortality. Reduced immunity and underlying medical conditions make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
(56 reference statements)
0
11
0
6
Order By: Relevance
“…The oral conditions that have been reported as rare and that have occurred in confirmed COVID-19 patients, are enlarged lymph nodes in the submandibular region, inflammation in the mouth, dry mouth, ageusia, herpetic lesions, desquamative gingivitis, tongue pain and blisters on the lip mucosa [ 8 ]. The prevention measures recommended for dental emergency care in Mexico are the following: give the patient pre-operative antimicrobial mouth-rinse (0.2% povidone iodine and 1% hydrogen peroxide) [ 9 , 10 ], avoid as possible the use of rotary equipment and triple syringe, use of rubber dam, disposable shoe covers, use of disposable gown, surgical goggles or face shield, use of N95 surgical mask and frequently cleaning and disinfecting public contact areas including door handles, chairs and washrooms [ 4 , 11 ]. Additionally, the American Dental Association (ADA) has published recommended preventive measures for dental care; however, dentists may not be aware of recent recommendations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oral conditions that have been reported as rare and that have occurred in confirmed COVID-19 patients, are enlarged lymph nodes in the submandibular region, inflammation in the mouth, dry mouth, ageusia, herpetic lesions, desquamative gingivitis, tongue pain and blisters on the lip mucosa [ 8 ]. The prevention measures recommended for dental emergency care in Mexico are the following: give the patient pre-operative antimicrobial mouth-rinse (0.2% povidone iodine and 1% hydrogen peroxide) [ 9 , 10 ], avoid as possible the use of rotary equipment and triple syringe, use of rubber dam, disposable shoe covers, use of disposable gown, surgical goggles or face shield, use of N95 surgical mask and frequently cleaning and disinfecting public contact areas including door handles, chairs and washrooms [ 4 , 11 ]. Additionally, the American Dental Association (ADA) has published recommended preventive measures for dental care; however, dentists may not be aware of recent recommendations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan instrument yang menghasilkan aerosol sebaiknya dihindari digantikan dengan instrument tangan seperti alat scaling manual atau ekskavator yang dikombinasikan dengan bahan penghilang karies chemomechanical seperti natrium hypoklorit (NaOCl) 8,14,19 . Posisi operator saat tindakan sebaiknya dilakukan dalam posisi jam 10 atau 11, posisi jam 8 harus dihindari, untuk menghindari percikan yang terjadi saat prosedur perawtan gigi dan bekerja dengan teknik four handed 21,27,30,31 . Penggunaan handpiece tanpa fungsi anti-retraksi harus di hindari 20,23,24 .…”
Section: Sebelum Melakukan Prosedur Perawatan Dokter Gigi Dan Asisten Diwajibkanunclassified
“…Healthcare providers are at a higher risk of transmission susceptibility of COVID-19 ( 2 , 3 ); among them, oral healthcare professionals are at the front line. Oral health problems are more likely to be seen in the geriatric age groups than in the other age groups ( 4 , 5 ). The geriatric population is prone to increased risk from COVID-19 because of psychological and pathological changes, decreased immune function, and existing comorbidity making them more susceptible to COVID-19 ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Malaysian national oral health survey of adults, it has been reported that 50.8% of the elderly aged 60 years and older geriatric patients had some form of oral prosthesis ( 11 ). The majority of prosthodontic procedures require direct contact with the patients and indirect contact with dental technicians and dental laboratories for the procedures which include dental casts, dental impressions, fabrication of removable prosthesis, and mock trials ( 4 , 5 ). The provision of prosthodontic care in geriatric patients could be urgent and/or emergency, depending on the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation